Bamboo foundation mat for rubble mound breakwaters on mud deposits - Kamali, B.; Hashim, Roslan (Academic Journals, 2010)
From geotechnical viewpoint, soft mud is generally characterised by low shear strength. As a consequence of this, construction activity on mudflats could be very difficult, costly and even impractical. In this study, bamboo culms that are inexpensive and locally abundant were introduced as a bedding material for a low crested rubble mound breakwater. Bamboo mats could be used as an alternative cost-effective foundation on mud deposits. This paper presents a case study of a shore protection work on an intertidal mudflat on the west coast of Peninsular Malaysia. Structural monitoring conducted since completion of construction indicates that the amount and rate of foundation settlement is substantially limited. The effective function of bamboo mats recommends replicating this approach in construction activities on the muddy beaches.